Morpho-Molecular and Phylogenetic Characterization of Hyalomma dromedarii Infesting Camels and Associated Protozoan Pathogens in Saudi Arabia - Abdulaziz Altwaim, Sarah; Kamaludeen, Juriah; Mohammed Alsaady ‎, Isra; Mohammed, Muhamad Azmi; Suliman Gattan, Hattan; Hamid Alruhaili, Mohammed; Saad Alghanmi, Maimonah; Ibraheem Azhar, Esam (Acta Scientiae Veterinariae, 2026)
Background: Ticks are major blood-feeding ectoparasitic arthropod vectors of zoonotic and veterinary pathogens, posing serious threats to livestock production, as well as animal and public health worldwide. In tropical and subtropical regions such as Saudi Arabia, one-humped camels (Camelus dromedarius) are important livestock hosts and are frequently infested with hard ticks, particularly species of the genus Hyalomma. These ticks are known vectors of several protozoan and bacterial pathogens of veterinary importance. However, despite their epidemiological relevance, comprehensive studies that integrate morphological identification, molecular characterization, and phylogenetic analysis of camel-infesting ticks, along with screening for associated protozoan pathogens, remain scarce. This study aimed to characterize Hyalomma dromedarii infesting camels in western and northwestern Saudi Arabia using morphological, molecular, and phylogenetic approaches, and to investigate the presence of selected tick-borne bacterial and protozoan pathogens. Materials, Methods & Results: In this study, Hyalomma specimens were collected from one-humped camels between 2021 and 2022 from 6 localities in Saudi Arabia (Alkhumrah, Brayman, Asfan, Dahaban, Duba, and Tabuk). The collected tick specimens were initially identified morphologically using standard keys and subsequently confirmed at the molecular level through genomic DNA extraction, followed by amplification and sequencing of the mitochondrial cytochrome c oxidase subunit I (cox1) gene via polymerase chain reaction (PCR). The extracted genomic DNA was further screened for protozoan pathogens using PCR targeting the 18S rDNA genes. Phylogenetic analysis was performed using the maximum likelihood method on the Cyberinfrastructure for Phylogenetic Research (CIPRES) server. A total of 218 tick specimens were collected from 48 infested camels, comprising 116 males and 102 females. All collected specimens were morphologically identified as Hyalomma dromedarii, which was supported by cox1 sequence analysis. In BLAST results, the obtained cox1 sequences showed maximum identity with H. dromedarii sequences reported from African, Middle Eastern, Asian, and Australian countries, and phylogenetically clustered with sequences of the same species. Notably, the extracted genomic DNA from H. dromedarii was screened for various pathogens, including Rickettsia spp., Anaplasma spp., Coxiella spp., Babesia spp., Theileria spp., and Hepatozoon spp. Among these, only protozoan species, specifically Theileria annulata and Hepatozoon canis DNA, were detected in the examined tick specimens. Co-detection of protozoan pathogens was observed in some samples, suggesting the circulation of multiple pathogens within camel-associated tick populations. In BLAST results, the obtained 18S rDNA sequences showed 100% identity with the corresponding species (T. annulata and H. canis) reported from various countries and phylogenetically clustered with the same species sequences. Discussion: This study provides integrated morphological, molecular, and phylogenetic data for Hyalomma dromedarii infesting one-humped camels in the western and northwestern regions of Saudi Arabia and confirms the dominance and genetic stability of this species across multiple study areas. The detection of T. annulata and H. canis highlights the potential epidemiological role of camel ticks in maintaining protozoan pathogens. These findings underscore the importance of continuous molecular surveillance to better understand the ecology, evolution, and pathogen transmission dynamics of camel-associated ticks in Saudi Arabia. Keywords: camel, cox1, Hyalomma dromedarii, protozoan, Saudi Arabia.